2019
DOI: 10.29252/nbr.6.3.326
|View full text |Cite
|
Sign up to set email alerts
|

Stipa richteriana (Poaceae) and Galium songaricum (Rubiaceae): two new additions of the Central Asian species to the flora of Iran

Abstract: Stipa richteriana and Galium songaricum are newly recorded species for the flora of Iran, collected from Binalood and Hezar-Masjed Mountains in Razavi Khorassan Province. The geographical distribution of both species is mainly confined to the Middle Asia. Morphological characters of two newly recorded species are compared with their close relatives. Notes on taxonomy, ecology, phytogeography, and conservation status of both species are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Moreover, the KK is a transitional zone connecting different phytogeographical units of the Irano-Turanian region such as Central Iranian, Afghan, Aralo-Caspian, and the Middle/Central Asian (Memariani, 2020). A comprehensive analysis of diversity and chorology of the flora of KK (Memariani et al, 2016a) and also recently recorded plant species from the area (see Memariani & Arjmandi, 2013;Behroozian et al, 2019) revealed that more than100 plant species (ca. 3.7% of the KK flora) have a range-restricted distribution mainly in the lowlands and/or mountains of the Middle/Central Asia with a disjunction in KK and some of them are connected to KK through the north of Afghanistan.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the KK is a transitional zone connecting different phytogeographical units of the Irano-Turanian region such as Central Iranian, Afghan, Aralo-Caspian, and the Middle/Central Asian (Memariani, 2020). A comprehensive analysis of diversity and chorology of the flora of KK (Memariani et al, 2016a) and also recently recorded plant species from the area (see Memariani & Arjmandi, 2013;Behroozian et al, 2019) revealed that more than100 plant species (ca. 3.7% of the KK flora) have a range-restricted distribution mainly in the lowlands and/or mountains of the Middle/Central Asia with a disjunction in KK and some of them are connected to KK through the north of Afghanistan.…”
Section: Introductionmentioning
confidence: 99%